The effect of investment regulatory changes on stock prices and trading volumes: Evidence from Iraq Stock Exchange - Mohammed, Mohammed Ahmed (2014)
This study investigates the effect of investment regulatory changes by examining the difference in stock prices and trading volume before and after the changes in the investment regulations in Iraq stock exchange in August 2007. It also examines the relationship between two economic factors (namely GDP and Inflation Rate) with stock prices and trading volume. This study utilizes data from 10 financial companies with 30 monthly observations covering the years 2006-2008. The current study employs market model to assess the investors’ reaction to the announcement and implementation of regulatory changes; and SSPS to provide descriptive analysis, Pearson correlation and T-Test for the examined variables. The results indicate that the stock prices moved towards a higher price after the regulation changes were implemented in August 2007 in which allow foreign investors to invest in Iraqi stocks. Their cumulative abnormal return is 5 percent. The increase in the prices of stocks in the Iraqi stock market after the implementation of the regulation indicated investors favour the new regulation. In addition, the trading volume and market capitalization ranking were dominated by the banking stocks among the selected financial companies. GDP and inflation is significantly and negatively correlated to CPI and CAR respectively. The companies were categorized between under-performed group and outperformed group (relative to AAR of 3.43 percent). The t-test indicates that there is a significant difference between the two types of the companies in their response to the regulatory change.